Influence of minor hydrocarbon seepage on sulfur cycling in marine subsurface sediments - E. Schnabel; A. Vuillemin; C. C. Laczny; B. J. Kunath; A. R. Soares; A. J. Probst; R. Di Primio; J. Kallmeyer (Biogeosciences)
All hydrocarbon (HC) reservoirs leak to some extent. When small quantities of HCs escape offshore reservoirs and migrate through overlying organic-poor marine sediments towards the surface, these HCs are often completely metabolized by microorganisms before reaching the sediment–water interface. However, these low and often unnoticed upward HC fluxes still influence the geochemistry of surrounding sediments and potentially stimulate metabolic activity by microbial populations in shallow subseafloor environments.